Multiple Temporalities of Household Labour: The Challenge of Assessing Women's Empowerment. Issue 2 (2nd October 2020) - Simon, Gregory L.; Peterson, Cody; Anderson, Emily; Berve, Brendan; Caturia, Marcelle; Rivera, Isaac
ABSTRACT: The economic empowerment of women remains a central feature of development projects worldwide. This article explores these empowerment aspirations by examining various temporal complexities related to two development projects in South India targeting individual cooking and fuel‐collection routines. It argues that three temporal considerations of household labour — polychronic time, collectivized time and hybrid labour/leisure time — are largely overlooked, thus challenging the appropriateness of empowerment strategies from the outset. By highlighting key household dynamics this study argues that efforts to pursue economic empowerment by members of the clean cookstove sector devalue unpaid labour and glorify waged work that is often tedious and mediated by powerful men. Further, waged work can be burdensomely added to pre‐existing unpaid domestic labour responsibilities. This common portrayal of empowerment by the clean cookstove sector can be viewed as facilitating the advancement of a neoliberal vision of rural women's livelihoods where empowerment and agency are reconfigured and incorporated into the problematic wage relations of capitalist economies. This view of empowerment, which privileges market participation, also overlooks many of the actually experienced positive effects of improved stoves; benefits which tend to be domestic, communal, routine, non‐economic and difficult to quantify. The article argues that conventional definitions and visions of 'empowerment' should be re‐evaluated to include forms of 'mundane agency'.